Partial vertical ownership in the presence of downstream competition - Fang, Fang; Jiang, Baojun; Sun, Jiong (Production and Operations Management, 2023)
Firms sometimes acquire partial ownership of their upstream suppliers. Such ownership entails no direct control over the target firm's decision‐making; however, both firms might change their pricing strategies after forming a partial ownership relationship. This paper studies the economic impacts of partial vertical ownership (PVO) in a market with downstream competition, where a manufacturer supplies two competing retailers. We find that dividend payments between firms can alter firms’ incentives in their operational decisions and, hence, serve as an “invisible hand” to downstream competition and vertical interaction. We show that a higher PVO percentage can have both positive and negative effects because the acquiring retailer's gain from PVO depends on not only its own sales but also the competitor's sales. Thus, the PVO decision (i.e., the percentage of ownership to acquire) has an inverted U‐shaped effect on the resulting profit for both the acquiring retailer and the manufacturer, which implies an intermediate PVO percentage in equilibrium. Second, the relative strength of the positive and negative effects depends on the acquiring retailer's competitive position. We show that the manufacturer prefers establishing PVO with the retailer with a valuation disadvantage because the disadvantaged retailer can obtain more benefits from PVO and is willing to pay higher than the competitor. Last, we find that consumers benefit from PVO when the acquiring retailer is the retailer with a valuation advantage but may become worse off when the disadvantaged retailer acquires PVO. Our research provides managers with guidance on the optimal PVO percentage and policymakers with insights on regulating PVOs for consumer protection.